CAPSULAR POLYSACCHARIDE OF AZOTOBACTER AGILIS - Cohen, Gary H. (1964)
Cohen, Gary H. (University of Vermont, Burlington), and Donald B. Johnstone. Capsular polysaccharide of Azotobacter agilis. J. Bacteriol. 88:1695–1699. 1964.—Capsular polysaccharide from Azotobacter agilis strain 132 was recovered from washed cells by alkaline digestion. The polysaccharide was purified by centrifugation, repeated alcohol precipitation, Sevag deproteinization, and treatment with ribonuclease and charcoal-cellulose. Methods of isolation and purification appeared to provide a polymer showing no evidence of heterogeneity when examined by chemical and physical methods. Colorimetric, paper chromatographic, and enzymatic analyses on both intact and acid-hydrolyzed polysaccharide indicated that the polymer contained galactose and rhamnose at a molar ratio of approximately 1.0:0.7. A sialic acid-like component was also present in the polysaccharide. The study shows significant differences in the chemical composition of the extra-cellular polysaccharide of A. agilis and that of A. vinelandii. This adds further biochemical evidence for the right of these species to independent status.